Construction of Chemical Libraries of Volatile Compounds by Combinatorial Synthesis of Homologous Mixtures: Alk‐4‐en‐1‐ols, Alk‐4‐enals and Methyl Alk‐4‐enoates. Issue 2 (19th January 2023) - Perrin, Coline; Baldovini, Nicolas
Abstract: A compound library of sixty six linear compounds, eleven representatives of six molecular families: ( E )‐ and ( Z )‐isomers of alk‐4‐en‐1‐ols, alk‐4‐enals, and methyl alk‐4‐enoates, was prepared by combinatorial syntheses to allow the creation of a mass spectral database directly usable for their identification in GC/MS analyses. We demonstrate here that compound libraries can be prepared by combinatorial syntheses using long linear synthetic sequences, i. e., eight step in the case of 4‐enals. The resulting mixtures of homologues are still perfectly exploitable to deliver the requested information such as clean mass spectra and good gas chromatographic retention indices. Abstract :